Discrete, Continuous, and Hybrid Petri Nets - David, René; Alla, Hassane (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This monograph presents a well written and clearly organized introduction in the standard methods of discrete, continuous and hybrid Petri Nets. Starting from the basics of Petri nets the book imparts an accurate understanding of continuous and hybrid Petri Nets. Preserving the consistency of basic concepts throughout the text it introduces a unified framework for all the models presented. The book is a scientific monograph as well as a didactic tutorial which is easy to understand due to many exercises with solutions, detailed figures and several case studies. It demonstrates that Petri nets are a deep, practical and alive field important for researchers, engineers and graduate students in engineering and computer science. Improvements and additions in this second edition have widely benefited from teaching, student questions, and various discussions with colleagues interested or involved in the topic.